2010
DOI: 10.1128/aac.00479-10
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Fluconazole-Resistant Candidemia

Abstract: Bloodstream infections (BSIs) due to Candida species are a serious complication in hospitalized patients. Candidemia is associated with a high mortality rate and has obvious effects on resource use (11). Over the past few decades, the incidence of candidemia has increased markedly (2, 3). Moreover, the increment of candidemia caused by Candida species other than Candida albicans is a common finding in recent series (3, 12). These species include C. glabrata and C. krusei, which tend to be more resistant to flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 32 publications
3
56
0
4
Order By: Relevance
“…Widespread use of triazoles in prophylactic and empirical treatment has led to an increase in Candida species with resistance to azoles. It was reported that previous FCZ treatment was an independent risk factor for candidemias, which are resistant to FCZ (17). Although differences are present in various studies, the rate of FCZ resistance ranges between 0.7% and 8.6% (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Widespread use of triazoles in prophylactic and empirical treatment has led to an increase in Candida species with resistance to azoles. It was reported that previous FCZ treatment was an independent risk factor for candidemias, which are resistant to FCZ (17). Although differences are present in various studies, the rate of FCZ resistance ranges between 0.7% and 8.6% (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have been associated with reduced survival in cancer patients with recent azole administration (17,38,45). The relationship between the increased incidence of these species and fluconazole prescription has been debated ever since the introduction of fluconazole as prophylaxis in hematology wards (1,15,33,46) and in ICUs (14). Interestingly, recent studies pointed out that a single dose of fluconazole was associated with an increased risk of candidemia due to non-C. albicans isolates (6) and noted a correlation between reduced fluconazole use and decreasing incidence of non-C. albicans candidemia (4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous azole exposure is an important risk factor for fungemia caused by fluconazole-resistant Candida isolates (28). However, the azole resistance of some clinical isolates of C. tropicalis may not be associated with previous exposure to azole agents (3).…”
Section: Discussionmentioning
confidence: 99%